Evaluation of Shatpada Fruit Fly Traps Versus Conventional Fruit Fly Traps in Citrus in India - Sandeep Singh; Srinivas Reddy; Ranjit Kadu; Y. V. Ingle; Sikha Deka; Raaj Kumar Kokoti; L. Ranjith Kumar; Aayush Kaushal; Deepa Bhagat; S. Priya Devi; Guranshpaul Singh; Ashok Kumar; et al. (Applied Fruit Science, 2026)

Advances in heavy metal removal from fruit juices: implications for food safety and quality control - G. Jeevarathinam; J. Deepa; Amarjit Singh Ningthoujam; Bedanta Rajbongshi; C. Nickhil; Shweta; Snigdha Chetia; Seema Ramniwas; S. Ganga Kishore; Davinder Pal Singh Oberoi; Sarvesh Rustagi; Syed Mohammed Basheeruddin Asdaq (Critical Reviews in Food Science and Nutrition, 2026)

Emerging technologies in watermelon juice Processing: Innovations in preservation and quality enhancement - G. Jeevarathinam; Vismaya K. Sachithanandhan; J. Deepa; V. Arun Prasath; S. Ganga Kishore; Punit Singh; Sarvesh Rustagi; Syed Mohammed Basheeruddin Asdaq (Food Control, 2026)

Deacidification of vegetable oils: advanced technologies, mechanistic insights, and emerging strategies - G. Jeevarathinam; R. Rahul; J. Deepa; N. Sharath Kumar; C.S. Neethu; G. Sarojini; V. Siva Shankar; Punit Singh; Davinder Pal Singh Oberoi; Sarvesh Rustagi; Syed Mohammed Basheeruddin Asdaq (Food Chemistry, 2026)

The influence of climate modes on long-term sea level variability of the Indian ocean with special emphasis on the Southern Annular Mode: A study based on Indian ocean sea level reconstructions - J. S. Deepa; C. Gnanaseelan; K. V. Anusree (Theoretical and Applied Climatology, 2025)

Tailored NiSx/BaNiO3 bilayer for enhanced oxygen evolution reaction in alkaline seawater - J. Junita; D. Jayalakshmi; S. Deepa Priya; Byung Chul Kim; John D. Rodney (Chemical Engineering Journal, 2025)

Experimental investigation of shrouded tomato storage systems in mitigating losses during long-distance transportation - G. Hari Pranesh; S. Ganga Kishore; P.L. Meenakshi; V. Arun Prasath; Madhuresh Dwivedi; J. Deepa; R. Pandiselvam; M. Arulkumar (Journal of Stored Products Research, 2025)

Using ultrasound and microbubble to enhance the effects of conventional cancer therapies in clinical settings - Deepa Sharma; Gregory J. Czarnota (Cancer and Metastasis Reviews, 2025)

On the skill of Indo-Pacific decadal sea level predictions and its connection with skilful AMO and PDO predictions - J. S. Deepa; C. Gnanaseelan (Climate Dynamics, 2024)

Steroids and Epicoccarines from Penicillium aurantiancobrunneum - Charmaine A. Lindsay; Choon Y. Tan; Deepa Krishnan; Dmitriy Uchenik; Gerardo D. Anaya Eugenio; Eric D. Salinas; Esperanza J. Carcache de Blanco; A. Douglas Kinghorn; Harinantenaina L. Rakotondraibe (Phytochemistry Letters, 2024)

Mechanical characterization of Rice Husk Ash incorporated bituminous concrete - Kallypalli SaiMadhu; Deepa Sasidharan; Kavinmathi Kadiroli; Bharath Gottumukkala; Geetha Sreekantan Parvathi; Amit J Solanki (Innovative Infrastructure Solutions, 2024)

Innovative agricultural diagnosis: DQRR-AFH algorithm model for effective leaf disease prevention and monitoring - S. L. Bharathi; N. Deepa; J. Sathya Priya; K. Muthulakshmi (Earth Science Informatics, 2024)

Generation of 3-aminopropanamide and its cluster formation with nucleation precursors- a theoretical exploration - J. Aswathi; Deepa Janardanan (Chemosphere, 2024)

Microstructure, rheological and water mobility behaviour of plant-based protein isolates (pea and quinoa) and locust bean gum mixtures - Deepa Agarwal; Esther H.-J. Kim; Limei Feng; Cath Wade; Gert-Jan Moggré; Marco P. Morgenstern; Duncan I. Hedderley (Food Research International, 2023)

A multicentre evaluation and expert recommendations of use of the newly developed BioFire Joint Infection polymerase chain reaction panel - Kordo Saeed; Nusreen Ahmad-Saeed; Rachel Annett; Gavin Barlow; Lucinda Barrett; Sara E. Boyd; Nicola Boran; Peter Davies; Harriet Hughes; Gwennan Jones; Laura Leach; Maureen Lynch; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
Septic arthritis is a serious condition with significant morbidity and mortality, routinely diagnosed using culture. The FDA has recently approved the rapid molecular BioFire® Joint Infection Panel (BJIP) for synovial fluid. We aimed to evaluate the BJIP compared to culture and its potential use in patient management. A multicentre retrospective evaluation of BJIP was conducted in the UK and Ireland. Positive percent agreement (PPA) and negative percent agreement (NPA) were calculated between the BJIP and routine culture. A multidisciplinary team (MDT) discussion addressing the optimal or potential case use of the assay practice was facilitated. Three hundred ninety-nine surplus synovial fluid samples (~ 70% from native joints) from eight centres were processed using BJIP in addition to routine culture. An increased yield of positive results was detected using BJIP compared to routine culture (98 vs 83), giving an overall PPA of 91.6% and overall NPA of 93% for the BJIP compared to culture results. The BJIP detected resistant markers and additional organisms that could influence antibiotic choices including Neisseria gonorrhoeae and Kingella kingae . The MDT agreed that the assay could be used, in addition to standard methods, in adult and children patients with specialist advice use based on local needs. Rapid results from BJIP were assessed as having potential clinical impact on patient management. Organisms not included in the panel may be clinically significant and may limit the value of this test for PJI.

Assessment of surface water quality during different tides and an anthropogenic impact on coastal water at Gulf of Kachchh, West Coast of India - Haresh Z. Panseriya; Haren B. Gosai; Deepa J. Gavali; Bharti P. Dave (Environmental Science and Pollution Research, 2022)

Water quality and probabilistic non-carcinogenic health risk of groundwater: a half decadal scenario change in Vadodara - Haresh Z. Panseriya; Deepa J. Gavali; Jayendra J. Lakhmapurkar; Anuva Saha; Priyal Gandhi (Environmental Geochemistry and Health, 2022)

Moths and butterflies on alien shores: Global biogeography of non‐native Lepidoptera - Richard Mally; Rebecca M. Turner; Rachael E. Blake; Gyda Fenn‐Moltu; Cleo Bertelsmeier; Eckehard G. Brockerhoff; Robert J. B. Hoare; Helen F. Nahrung; Alain Roques; Deepa S. Pureswaran; Takehiko Yamanaka; Andrew M. Liebhold (Journal of Biogeography, 2022)
Aim Lepidoptera is a highly diverse, predominantly herbivorous insect order, with species transported to outside their native range largely facilitated by the global trade of plants and plant‐based goods. Analogous to island disharmony, we examine invasion disharmony, where species filtering during invasions increases systematic compositional differences between native and non‐native species assemblages, and test whether some families are more successful at establishing in non‐native regions than others. Location Hawaii, North America, Galapagos, Europe, South Africa, South Korea, Japan, Nansei Islands, Ogasawara Islands, Australia, New Zealand. Taxon Lepidoptera. Methods We compared numbers of non‐native, unintentionally introduced Lepidoptera species with the land area of 11 regions worldwide. Differences among native and non‐native assemblages in the distribution of species among families were investigated using ordination analysis. We tested whether invasion disharmony is explained by propagule pressure (proxied by species richness in border interceptions) and if families were associated with specific trade commodities. Results In total, 741 non‐native Lepidoptera species, accounting for 0.47% of the global diversity of lepidopterans, are established in at least one of the 11 regions. Crambidae, Pyralidae, Tineidae and Gracillariidae were particularly successful invaders, whereas the two most species‐rich families, Erebidae and Geometridae, were under‐represented among non‐native Lepidoptera. Much of the variation in species numbers in the native, and less so in the non‐native assemblages could be attributed to land area. Although native assemblages were similar among nearby regions, non‐native assemblages were not, suggesting geography had little effect on invasion disharmony. Comparison of established with intercepted species revealed that macromoth families were generally under‐represented in establishments, whereas several micromoth families were under‐represented in interceptions. This discrepancy may relate to greater detectability of larger species or high propagule pressure via associations with specific invasion pathways. Main conclusions Invasion disharmony in Lepidoptera appears to be driven by processes unrelated to the success of native assemblages. While native assemblages developed through long‐term evolutionary radiation, the composition of non‐native assemblages is driven by differential invasion pathways and traits affecting the establishment of founder populations that vary among families.

Rapid assessment of insect pollination services to inform decision‐making - Fabrizia Ratto; Tom D. Breeze; Lorna J. Cole; Michael P. D. Garratt; David Kleijn; Bill Kunin; Denis Michez; Rory O'Connor; Jeff Ollerton; Robert J. Paxton; Guy M. Poppy; Simon G. Potts; et al. (Conservation Biology, 2022)
Pollinator declines have prompted efforts to assess how land‐use change affects insect pollinators and pollination services in agricultural landscapes. Yet many tools to measure insect pollination services require substantial landscape‐scale data and technical expertise. In expert workshops, 3 straightforward methods (desk‐based method, field survey, and empirical manipulation with exclusion experiments) for rapid insect pollination assessment at site scale were developed to provide an adaptable framework that is accessible to nonspecialist with limited resources. These methods were designed for TESSA (Toolkit for Ecosystem Service Site‐Based Assessment) and allow comparative assessment of pollination services at a site of conservation interest and in its most plausible alternative state (e.g., converted to agricultural land). We applied the methods at a nature reserve in the United Kingdom to estimate the value of insect pollination services provided by the reserve. The economic value of pollination services provided by the reserve ranged from US$6163 to US$11,546/year. The conversion of the reserve to arable land would provide no insect pollination services and a net annual benefit from insect‐pollinated crop production of approximately $1542/year (US$24∙ha –1 ∙year –1 ). The methods had wide applicability and were readily adapted to different insect‐pollinated crops: rape ( Brassica napus ) and beans ( Vicia faba ) crops. All methods were rapidly employed under a low budget. The relatively less robust methods that required fewer resources yielded higher estimates of annual insect pollination benefit.

Inferring ecological strategies of Psenopsis spp. (Teleostei: Centrolophidae) inhabiting Indian waters from morphological features - K. V. Aneesh Kumar; M. P. Rajeeshkumar; M. Hashim; K. P. Deepa; J. L. Otero-Ferrer; N. Saravanane; Sujitha Thomas; K. K. Bineesh; V. M. Tuset (Marine Biology Research, 2022)

Agro-morphological variability and genetic diversity in linseed (Linum usitatissimum L.) germplasm accessions with emphasis on flowering and maturity time - Ankit Saroha; Deepa Pal; Vikender Kaur; Sandeep Kumar; Arti Bartwal; J. Aravind; J. Radhamani; S. Rajkumar; Rajesh Kumar; Sunil S. Gomashe; Abhishek Sengupta; Dhammaprakash Pandhari Wankhede (Genetic Resources and Crop Evolution, 2022)

Atmospheric Aerosol Scattering Coefficients in a Broad Visible Spectral Region - R. Arun; P. Anoop; S. John; J. Chen; V. Deepa; R. Varma (Aerosol Science and Engineering, 2021)

Single-Turnover Variable Chlorophyll Fluorescence as a Tool for Assessing Phytoplankton Photosynthesis and Primary Productivity: Opportunities, Caveats and Recommendations - Nina Schuback; Philippe D. Tortell; Ilana Berman-Frank; Douglas A. Campbell; Aurea Ciotti; Emilie Courtecuisse; Zachary K. Erickson; Tetsuichi Fujiki; Kimberly Halsey; Anna E. Hickman; Yannick Huot; Maxime Y. Gorbunov; et al. (Frontiers in Marine Science, 2021)
Phytoplankton photosynthetic physiology can be investigated through single-turnover variable chlorophyll fluorescence (ST-ChlF) approaches, which carry unique potential to autonomously collect data at high spatial and temporal resolution. Over the past decades, significant progress has been made in the development and application of ST-ChlF methods in aquatic ecosystems, and in the interpretation of the resulting observations. At the same time, however, an increasing number of sensor types, sampling protocols, and data processing algorithms have created confusion and uncertainty among potential users, with a growing divergence of practice among different research groups. In this review, we assist the existing and upcoming user community by providing an overview of current approaches and consensus recommendations for the use of ST-ChlF measurements to examine in-situ phytoplankton productivity and photo-physiology. We argue that a consistency of practice and adherence to basic operational and quality control standards is critical to ensuring data inter-comparability. Large datasets of inter-comparable and globally coherent ST-ChlF observations hold the potential to reveal large-scale patterns and trends in phytoplankton photo-physiology, photosynthetic rates and bottom-up controls on primary productivity. As such, they hold great potential to provide invaluable physiological observations on the scales relevant for the development and validation of ecosystem models and remote sensing algorithms.

The sea level variability and its projections over the Indo‐Pacific Ocean in CMIP5 models - J. S. Deepa; C. Gnanaseelan; Anant Parekh (Climate Dynamics, 2021)

Multidecadal to decadal variability in the equatorial Indian Ocean subsurface temperature and the forcing mechanisms - Sandeep Mohapatra; C. Gnanaseelan; J. S. Deepa (Climate Dynamics, 2020)

Revealing changes in the microbiome of Symbiodiniaceae under thermal stress - Emma F. Camp; Tim Kahlke; Matthew R. Nitschke; Deepa Varkey; Nerissa L. Fisher; Lisa Fujise; Samantha Goyen; David J. Hughes; Caitlin A. Lawson; Mickael Ros; Stephen Woodcock; Kun Xiao; et al. (Environmental Microbiology, 2020)
Summary Symbiodiniaceae are a diverse family of marine dinoflagellates, well known as coral endosymbionts. Isolation and in vitro culture of Symbiodiniaceae strains for physiological studies is a widely adopted tool, especially in the context of understanding how environmental stress perturbs Symbiodiniaceae cell functioning. While the bacterial microbiomes of corals often correlate with coral health, the bacterial communities co‐cultured with Symbiodiniaceae isolates have been largely overlooked, despite the potential of bacteria to significantly influence the emergent physiological properties of Symbiodiniaceae cultures. We examined the physiological response to heat stress by Symbiodiniaceae isolates (spanning three genera) with well‐described thermal tolerances, and combined these observations with matched changes in bacterial composition and abundance through 16S rRNA metabarcoding. Under thermal stress, there were Symbiodiniaceae strain‐specific changes in maximum quantum yield of photosystem II (proxy for health) and growth rates that were accompanied by changes in the relative abundance of multiple Symbiodiniaceae‐specific bacteria. However, there were no Symbiodiniaceae‐independent signatures of bacterial community reorganisation under heat stress. Notably, the thermally tolerant Durusdinium trenchii (ITS2 major profile D1a) had the most stable bacterial community under heat stress. Ultimately, this study highlights the complexity of Symbiodiniaceae‐bacteria interactions and provides a first step towards uncoupling their relative contributions towards Symbiodiniaceae physiological functioning.

Unsustainable trade-offs: provisioning ecosystem services in rapidly changing Likangala River catchment in southern Malawi - Deepa Pullanikkatil; Penelope J. Mograbi; Lobina Palamuleni; Tabukeli Ruhiiga; Charlie Shackleton (Environment, Development and Sustainability, 2020)

Biases in the Tropical Indian Ocean subsurface temperature variability in a coupled model - Rashmi Kakatkar; C. Gnanaseelan; Jasti S. Chowdary; J. S. Deepa; Anant Parekh (Climate Dynamics, 2019)

The Tropical Indian Ocean decadal sea level response to the Pacific Decadal Oscillation forcing - J. S. Deepa; C. Gnanaseelan; Sandeep Mohapatra; J. S. Chowdary; A. Karmakar; Rashmi Kakatkar; Anant Parekh (Climate Dynamics, 2019)

Synthesis of magnetic carbon nanocomposites by hydrothermal carbonization and pyrolysis - M. T. H. Siddiqui; Sabzoi Nizamuddin; Humair Ahmed Baloch; N. M. Mubarak; Deepa K. Dumbre; Inamuddin; Abdullah M. Asiri; A. W. Bhutto; Madapusi Srinivasan; G. J. Griffin (Environmental Chemistry Letters, 2018)

Impact of nitrogen availability upon the electron requirement for carbon fixation in Australian coastal phytoplankton communities - David J. Hughes; Deepa Varkey; Martina A. Doblin; Tim Ingleton; Allison Mcinnes; Peter J. Ralph; Virginie van Dongen‐Vogels; David J. Suggett (Limnology and Oceanography, 2018)
Nitrogen (N) availability affects phytoplankton photosynthetic performance and regulates marine primary production (MPP) across the global coast and oceans. Bio‐optical tools including Fast Repetition Rate fluorometry (FRRf) are particularly well suited to examine MPP variability in coastal regions subjected to dynamic spatio‐temporal fluctuations in nutrient availability. FRRf determines photosynthesis as an electron transport rate through Photosystem II (ETR PSII ), requiring knowledge of an additional parameter, the electron requirement for carbon fixation ( K C ), to retrieve rates of CO 2 ‐fixation. K C strongly depends upon environmental conditions regulating photosynthesis, yet the importance of N‐availability to this parameter has not been examined. Here, we use nutrient bioassays to isolate how N (relative to other macronutrients P, Si) regulates K C of phytoplankton communities from the Australian coast during summer, when N‐availability is often highly variable. K C consistently responded to N‐amendment, exhibiting up to a threefold reduction and hence an apparent increase in the efficiency with which electrons were used to drive C‐fixation. However, the process driving this consistent reduction was dependent upon initial conditions. When diatoms dominated assemblages and N was undetectable (e.g., post bloom), K C decreased predominantly via a physiological adjustment of the existing community to N‐amendment. Conversely, for mixed assemblages, N‐addition achieved a similar reduction in K C through a change in community structure toward diatom domination. We generate new understanding and parameterization of K C that is particularly critical to advance how FRRf can be applied to examine C‐uptake throughout the global ocean where nitrogen availability is highly variable and thus frequently limits primary productivity.

The interannual sea level variability in the Indian Ocean as simulated by an Ocean General Circulation Model - J. S. Deepa; C. Gnanaseelan; R. Kakatkar; A. Parekh; J. S. Chowdary (International Journal of Climatology, 2018)
Limited coverage of tide gauge observations and limited length record of altimeter observations remain inadequate for the Indian Ocean sea level variability studies especially for longer periods. This study takes advantage of Ocean General Circulation Model (OGCM) simulations and ocean reanalysis to explore the interannual variability of sea level in the Indian Ocean. The model simulated sea level anomalies display good correlation with altimetry and reanalysis products. This consistency in model simulations with observations and reanalysis highlights the potential use of this OGCM in understanding the sea level variability. Analysis reveals that co‐occurrence years (years when Indian Ocean Dipole (IOD) and El Niño events co‐occur) contribute significantly towards the interannual variability in the Indian Ocean compared to pure IOD or El Niño events, and are characterized by persistent generation of open ocean downwelling, with maximum signals in the 10° to 5°S region. The OGCM experiments are carried out by modulating the forcing fields over the Pacific and the Indian Ocean to understand the physical mechanisms causing sea level variability. The experiments suggest that the remote forcing from the Pacific Ocean via Indonesian ThroughFlow (ITF) induce significant sea level changes in the southern Indian Ocean only with variability mostly in the decadal time scales and the northern and equatorial Indian Ocean are not affected by ITF. This study also shows that El Niño and IOD‐induced variations in zonal wind stress and wind stress curl mainly contribute the interannual sea level variations in the Indian Ocean. The forcing associated with the co‐occurrence years are multi‐phased with coastal and open ocean forcing. Whereas the pure IOD and El Nino forcing is mainly found only over the open ocean. The decadal variability in the ENSO is primarily responsible for the decadal sea level variability in the Indian Ocean by modulating ITF transport.

Indian summer monsoon rainfall variability during 2014 and 2015 and associated Indo-Pacific upper ocean temperature patterns - Rashmi Kakatkar; C. Gnanaseelan; J. S. Chowdary; Anant Parekh; J. S. Deepa (Theoretical and Applied Climatology, 2018)

A new mouse model of frailty: the Cu/Zn superoxide dismutase knockout mouse - Sathyaseelan S. Deepa; Shylesh Bhaskaran; Sara Espinoza; Susan V. Brooks; Anne McArdle; Malcolm J. Jackson; Holly Van Remmen; Arlan Richardson (GeroScience, 2017)

The effect of flavanol-rich cocoa on cerebral perfusion in healthy older adults during conscious resting state: a placebo controlled, crossover, acute trial - Daniel J. Lamport; Deepa Pal; Christina Moutsiana; David T. Field; Claire M. Williams; Jeremy P. E. Spencer; Laurie T. Butler (Psychopharmacology, 2015)

An exploratory analysis linking neuropsychological testing to quantification of tractography using High Definition Fiber Tracking (HDFT) in military TBI - Nora Presson; Sue R. Beers; Lisa Morrow; Lauren M. Wagener; William A. Bird; Gina Van Eman; Deepa Krishnaswamy; Joshua Penderville; Allison J. Borrasso; Steven Benso; Ava Puccio; Catherine Fissell; et al. (Brain Imaging and Behavior, 2015)

Loss of P2Y2 Nucleotide Receptors Enhances Early Pathology in the TgCRND8 Mouse Model of Alzheimer's Disease - Deepa Ajit; Lucas T. Woods; Jean M. Camden; Christina N. Thebeau; Farid G. El-Sayed; Glen W. Greeson; Laurie Erb; Michael J. Petris; Douglas C. Miller; Grace Y. Sun; Gary A. Weisman (Molecular Neurobiology, 2014)

Genetic dissection of drought tolerance in chickpea (Cicer arietinum L.) - Rajeev K. Varshney; Mahendar Thudi; Spurthi N. Nayak; Pooran M. Gaur; Junichi Kashiwagi; Lakshmanan Krishnamurthy; Deepa Jaganathan; Jahnavi Koppolu; Abhishek Bohra; Shailesh Tripathi; Abhishek Rathore; Aravind K. Jukanti; et al. (Theoretical and Applied Genetics, 2014)

Adoptive transfer of antigen-specific T-cells of donor type for immunotherapy of viral infections following allogeneic hematopoietic cell transplants - Richard J. O’Reilly; Ekaterina Doubrovina; Deepa Trivedi; Aisha Hasan; Wouter Kollen; Guenther Koehne (Immunologic Research, 2007)

The effects of acute tyrosine and phenylalanine depletion on spatial working memory and planning in healthy volunteers are predicted by changes in striatal dopamine levels - Mitul A. Mehta; Deepa Gumaste; Andrew J. Montgomery; Sarah F. B. McTavish; Paul M. Grasby (Psychopharmacology, 2005)

Effect of methyl isocyanate (MIC) on rat erythrocytes - Deepa Agrawal; G. S. D. Gupta; J. S. Shukla; K. K. Dutta; P. K. Ray (Archives of Toxicology, 1990)